Enhancing Sleep Quality in Hypertension Patients: The Role of a HiAl (Hypertension Alert) Treatment - Sya'id, Achmad; Tursina, Hella Meldy; boonyaporn , Tippawan (Jurnal Kesehatan dr. Soebandi, 2026)
Background: Poor rest quality could be a frequent comorbidity among people with hypertension, contributing to negative cardiovascular conditions and decreased quality of life. This research assesses the significance of the HiAl (Hypertension Alert) intercession in improving rest quality among hypertensive patients in Jatisari, Jember, east Java.  Methods: This true experimental study selected one hundred registrants diagnosed with hypertension (50 registrants in the intervention team and the rest in the absence of the intervention team), selected through a straightforward random sampling technique. Participants were randomly assigned to either the intervention team or the rest in the absence of the intervention team receiving usual care from their attending physicians. The HiAl treatment included autonomous motivation, relatedness to health services, and perception of self-competence. Sleep quality was measured at baseline and the start of the research before treatment for both teams using the Pittsburgh Sleep Quality Index (PSQI) one month following the intervention. Results:   People who took part in the treatment experienced a statistically significant improvement in PSQI scores compared to the absence of an intervention team (24% before treatment and 76% after treatment people who took part in the intervention showing increasing in sleep quality, p = 0,002 using Wilcoxon signed-rank test). Conclusions: The findings indicate that the HiAl intervention is an effective approach for enhancing sleep quality in individuals with hypertension. HiAl may serve as a valuable tool for hypertension management and cardiovascular health promotion. Further research is warranted to assess its long-term impact and cost-effectiveness.